Surface characterisation of PEO‐like microstructures by means of ToF‐SIMS, XPS and SPR. (15th June 2012) - Perez‐Roldan, M.; Colpo, P.; Gilliland, D.; Ceccone, G.; Rossi, F.
<x xml:space="preserve">Abstract</x> In this work, we present a method to produce micro and nanostructured surfaces containing bioadhesive features embedded in an antifouling matrix. These surfaces are fabricated by combining plasma polymerization and electron beam lithography. This combination allows the fabrication of structured surfaces in just two steps and without the use of solvents. ToF‐SIMS analysis demonstrates that the e‐beam treatment induces a chemical change at the surface depending upon the radiation dose employed. In particular, a decrease of peaks characteristic of the PEO‐like fragments (e.g. CH3O+, C3H7O+, C3H5O2+) and a correspondent increase of hydrocarbon moieties such as C2H3+ and C3H3+ is observed in the irradiated zones. These results are supported by XPS analysis that indicate a slight reduction of the intensity of the C–O component in the C1s core level spectrum after irradiation similar to that observed in UV‐treated PEO‐like films. Experiments with proteins show a preferential adhesion of the biomolecules to the irradiated zone indicating the good potential of this technique for the development of nanostructured biosensing platforms. Copyright © 2012 John Wiley & Sons, Ltd.